Numerical investigation of coupled density‐driven flow and hydrogeochemical processes below playas. Issue 11 (28th November 2015) - Hamann, Enrico; Post, Vincent; Kohfahl, Claus; Prommer, Henning; Simmons, Craig T.
Abstract: Numerical modeling approaches with varying complexity were explored to investigate coupled groundwater flow and geochemical processes in saline basins. Long‐term model simulations of a playa system gain insights into the complex feedback mechanisms between density‐driven flow and the spatiotemporal patterns of precipitating evaporites and evolving brines. Using a reactive multicomponent transport model approach, the simulations reproduced, for the first time in a numerical study, the evaporite precipitation sequences frequently observed in saline basins ("bull's eyes"). Playa‐specific flow, evapoconcentration, and chemical divides were found to be the primary controls for the location of evaporites formed, and the resulting brine chemistry. Comparative simulations with the computationally far less demanding surrogate single‐species transport models showed that these were still able to replicate the major flow patterns obtained by the more complex reactive transport simulations. However, the simulated degree of salinization was clearly lower than in reactive multicomponent transport simulations. For example, in the late stages of the simulations, when the brine becomes halite‐saturated, the nonreactive simulation overestimated the solute mass by almost 20%. The simulations highlight the importance of the consideration of reactive transport processes for understanding and quantifying geochemical patterns, concentrations of individual dissolved solutes, and evaporite evolution. Key Points: Coupled groundwater flow and reactive processes in playa basins were studied numerically Spatiotemporal evaporite sequences were simulated, physicochemical interactions were determined Single‐species transport models replicated principle flow patterns but misestimated the salinization